RAGAM BAHASA DALAM MEDIA SOSIAL TIKTOK: AKUN GERALD VINCENT DAN IDOEL IMOETS - Hasby Fauzan Ode; La Yani Konisi; Rachman (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the language variations used by speakers in the comments sections of the TikTok accounts @Gerald Vincent and @Idoel Imoets. The research background is based on the role of language as a means of communication that continues to evolve and adapt to the needs of its users, particularly in digital interactions on social media. The method used was descriptive qualitative, using reading and note-taking techniques and documentation through screenshots of comments containing elements of language variations. The data obtained were then selected, classified, and analyzed to identify the types of language variations based on the speakers. The results show that of the eight types of language variations, only three were found in TikTok comments: slang, colloquial, and vulgar, with 41 slang words, 21 colloquial words, and 3 vulgar words, respectively. Acrolect, basilect, jargon, argot, and ken did not appear in the data. These findings illustrate the variety of Indonesian language developing in the digital space and reflect the communication patterns of the younger generation. This research is expected to contribute to the development of linguistics, particularly in the study of Indonesian Language and Literature Education.